Correlação entre produção de feijão e atributos físicos de um Latossolo em Mato Grosso do Sul - Montanari, Rafael; Pellin, Douglas Martins Pereira; Silva Júnior, Carlos Antonio Da; Carvalho, Morel De Passos E [UNESP]; Gioia, Máila Terra; Dalchiavon, Flávio Carlos; Paz González, Antonio (Universidade Federal de Viçosa (UFV), 2013)
In Brazil, common bean is in one of the most representative economic crops, not only because of its growing area but also because of the economic value of its production. In the crop year 2006/07, in Selvíria (MS), we analyzed the common bean yield as a function of some physical attributes of a Typic Acrustox in minimum tillage and center pivot irrigation system. The aim of this work was to evaluate among the soil physical attributes, under minimum tillage, those that better explain the variability of bean yield using the Pearson and spatial correlations,. A geostatistical grid was installed to collect data from soil and plants, with 117 sampling points in an area of 2025 m² and homogeneous slope of 0.055 m m-1. The results showed a low yield of bean, which occurred probably due to a lower density of plants that the system provided. Thus, for the minimum tillage system, the bean yield could be explained as a function of total porosity and bulk density.

No Brasil, a cultura do feijoeiro é uma das mais representativas explorações agrícolas, não só pela área de cultivo, como também pelo valor econômico de sua produção. No ano agrícola de 2006/07, no município de Selvíria (MS), foi analisada a produtividade de grãos do feijoeiro, em função de alguns atributos físicos de um Latossolo Vermelho distroférrico, em sistema de cultivo mínimo e irrigado com pivô central. Este trabalho objetivou avaliar, dentre os atributos físicos do solo, sob cultivo mínimo, aqueles que melhor expliquem, pela correlação de Pearson e espacialmente, a variabilidade da produtividade de grãos de feijão. Para tanto, foi instalada uma malha geoestatística, para a coleta de dados do solo e da planta, com 117 pontos amostrais, numa área de 2025 m² e declive homogêneo de 0,055 m m-1, 5%. Os resultados mostraram que houve baixa produtividade de grãos do feijoeiro, ocorrida provavelmente por causa de uma menor densidade de plantas que esse sistema proporcionou. Dessa forma, para o sistema de cultivo mínimo do solo, a produtividade de feijão pôde ser explicada, em função da porosidade total e da densidade do solo.
Correlation between common bean production and physical attributes of an Oxisol in Mato Grosso do Sul State, Brazil
Keywords: sistema de manejo; resistência à penetração; umidade; densidade do solo; Phaseolus vulgaris L; management system; penetration resistance; soil moisture; bulk density; Phaseolus vulgaris L